2018
DOI: 10.3390/dj6040066
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Dental Implant Surfaces by the Er:YAG Laser Beam: A Comparative in Vitro Study of Various Protocols

Abstract: Oral rehabilitation with dental implants has revolutionized the field of dentistry and has been proven to be an effective procedure. However, the incidence of peri-implantitis has become an emerging concern. The efficacy of the decontamination of the implant surface, by means of lasers, is still controversial. Previous studies have revealed a reduction in osteoblast adhesion to carbon-contaminated implant surfaces. This in-vitro study aimed to evaluate the decontamination of failed implants by assessing the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
(82 reference statements)
0
20
0
1
Order By: Relevance
“…Unfortunately, the PDT allows germs destruction without any implant surface cleaning. On the other hand, Er:YAG (Erbium-doped yttrium aluminium garnet) laser (laser irradiation with several passages showed promising results in the cleaning of implant surfaces [17]. Though, the reduced flexibility of the Er:YAG laser fiber is a limitation of its use in the deep or complex periimplantitis pockets.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the PDT allows germs destruction without any implant surface cleaning. On the other hand, Er:YAG (Erbium-doped yttrium aluminium garnet) laser (laser irradiation with several passages showed promising results in the cleaning of implant surfaces [17]. Though, the reduced flexibility of the Er:YAG laser fiber is a limitation of its use in the deep or complex periimplantitis pockets.…”
Section: Introductionmentioning
confidence: 99%
“…These surface alterations were able to slow down the cellular proliferation, but did not alter the cellular differentiation. On the contrary, Wakim et al have found no significant alteration on SLA titanium surfaces after multiple Er: YAG treatments with irradiation energy 50 mJ, 30 Hz frequency, 1.5 W power output, and 3.76 J/cm 2 energy density, but in this protocol, a super short pulse of 50 us was applied [46]. As a result, reduction to surface micro-roughness could delay or prevent bone bacterial adhesion.…”
Section: Discussionmentioning
confidence: 90%
“…The bacteria‐cultivated titanium disk is a common in vitro experimental model for implant surface debridement in previous studies. Recently, clinical failed implants were used as a better alternative for the comparison of different decontamination protocols (Hakki et al., 2017; Nejem Wakim et al., 2018; Rosen et al., 2018), which provide a more similar contaminated situation in clinical practice, including the calculus, bone debris, soft tissue, residual proteinaceous material and dry stains (Esposito et al., 1999;; Shibli et al., 2004, 2005). However, as the major limitation of the present study, the biofilm deposits had not been evaluated in the methodological approaches utilized.…”
Section: Discussionmentioning
confidence: 99%